2021
DOI: 10.1101/2021.08.17.21262119
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ambulatory Duchenne Muscular Dystrophy Children: Cross-sectional Correlation between Function, Quantitative Muscle Ultrasound and MRI

Abstract: Introduction/Aims: Duchenne muscular dystrophy (DMD) is a progressive genetic muscle disease. Quantitative muscle ultrasound (MUS), muscle MRI, and functional tools are important to delineate characteristics of muscle involvement. We aimed to establish correlations between clinical/functional and above-named imaging tools respecting their diagnostic and prognostic role in DMD children. Methods: A Prognostic cross-sectional retrospective study of 27 steroid-naive, ambulant male children/adolescents with genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…A significant higher difference in the median and IQR of the total score of GSGC of patients with grade IV modified Heckmatt scale was found in comparison to grade II and III (15 [12][13][14][15][16][17] vs. 8 [7][8][9][10], 11 [11][12][13], p < 0.001).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant higher difference in the median and IQR of the total score of GSGC of patients with grade IV modified Heckmatt scale was found in comparison to grade II and III (15 [12][13][14][15][16][17] vs. 8 [7][8][9][10], 11 [11][12][13], p < 0.001).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it has the potential to act as a substitute to functional assessment tools. 12 The aim of the current research was to study the correlation between GSGC (Gait, Stairs, Gower, Chair) motor functional score and the US findings of RF (modified Heckmatt and quantitative gray scale analysis). In view of the emerging therapeutic interventions for DMD, more valid tools for clinical assessment of patients are entailed.…”
Section: Introductionmentioning
confidence: 99%
“…6 This may be explained by the fact that the 6 MWT and muscle strength of the knee extensor have a negative and significant correlation with muscle fat. 21,26 Thus, as the disease progresses, the amount of fat in the muscle tissue increases, emphasizing knee extensor weakness and, consequently, worsening of the patient's performance on the 6 MWT.…”
Section: Discussionmentioning
confidence: 99%
“…The decline in walking ability measured by the 6 MWT occurs despite small changes in strength values of the knee extensor muscles across 1 year of longitudinal evaluation 6 . This may be explained by the fact that the 6 MWT and muscle strength of the knee extensor have a negative and significant correlation with muscle fat 21,26 . Thus, as the disease progresses, the amount of fat in the muscle tissue increases, emphasizing knee extensor weakness and, consequently, worsening of the patient's performance on the 6 MWT.…”
Section: Discussionmentioning
confidence: 99%
“…In-depth characterization of skeletal as well as cardiac involvement in cDMD deserves investigation, and advanced imaging techniques could facilitate this. 5,[9][10][11][12][13][14][15] For instance, cardiac magnetic resonance imaging (MRI) studies revealed myocardial fibrosis in up to 49% of cDMD (even in early stages), compared with 5% of noncarriers, highlighting the importance of imaging follow-up of this population. 15 Fornander et al 8 found in a cross-sectional study that both clinically symptomatic and asymptomatic cDMD have a higher fat fraction in muscles detectable by magnetic resonance imaging.…”
Section: Introductionmentioning
confidence: 99%